OPTIMALISASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL MEANS-ENDS ANALYSIS di KELAS VIII - Reny Wahyuni; Efuansyah E. (LP4MK STKIP PGRI Lubuklinggau, 2019)
This research aims to determine the mathematical problem solving abilities of eight grade students of Junior High School Number 2 Lubuklinggau after attending learning using the Means-Ends Analysis learning model in the good category. The population in this research were all eighth grade students of Junior High School Number 2 Lubuklinggau in the 2017/2018 academic year with research samples VIII.5. The design used in this study was a pretest-posttest control group design. Data collection techniques use a test of 5 questions which refers to indicators of mathematical problem solving abilities. Based on data analysis using the normality test and hypothesis testing data, it was found that obtained = 7.91 at the level of confidence α = 0.05 and = 1.671. So the results show that the problem solving abilities of eight grade students Junior High School Number 2 Lubuklinggau are in the good category with an average score of 7.24.